2020
DOI: 10.1002/sce.21567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a learning progression for the solar system: Progress along gravity and dynamical properties dimensions

Abstract: We previously proposed a hypothetical learning progression around the disciplinary core idea of the Solar System and its formation as a first step in a research program to begin to fill this gap and address questions of student learning in this domain. In this study, we evaluate the effectiveness of two dimensions within the learning progression, dynamical properties and gravity, in describing change in how student reason in the domain across the course of their 14‐week astronomy unit. A sample of sixth‐grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
(69 reference statements)
1
6
0
1
Order By: Relevance
“…Section Gravity shows that students at all levels had a fragmented understanding of the concepts involved in the questions. These results are consistent with other studies (Bar et al, 2016;Kavanagh & Sneider, 2007;Palmer, 2001;Plummer et al, 2020;Ruggiero et al, 1985) in which secondary students also showed alternative conceptions of weightlessness, factors that affect gravity and the role it plays in free-fall motion. The alternative ideas found in this study are also connected with a lack of understanding of other fundamental topics such as speed, acceleration, force, magnetism and mass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Section Gravity shows that students at all levels had a fragmented understanding of the concepts involved in the questions. These results are consistent with other studies (Bar et al, 2016;Kavanagh & Sneider, 2007;Palmer, 2001;Plummer et al, 2020;Ruggiero et al, 1985) in which secondary students also showed alternative conceptions of weightlessness, factors that affect gravity and the role it plays in free-fall motion. The alternative ideas found in this study are also connected with a lack of understanding of other fundamental topics such as speed, acceleration, force, magnetism and mass.…”
Section: Discussionsupporting
confidence: 92%
“…The idea of gravity as existing only on Earth was also found by Asghar and Libarkin (2010), in which half of the students involved in the research thought that gravity is only related to Earth and 93% believed that gravity is an outside force. Interestingly, Plummer et al (2020) found that even after instruction, 46% of the students still believed that not all celestial bodies in the Solar System have gravity.…”
Section: Students' Understanding Of Astronomymentioning
confidence: 99%
“…Yet at the same time Plummer (2009b) reminds us that in the case of children it is beneficial to learn not only the heliocentric (or more generically allocentric) perspective but also the geocentric perspective, that is, the apparent movements. Plummer (2009a) highlights that "the patterns of motion of the celestial objects, exhibited on a daily, monthly, and yearly basis, are among the most fundamental aspects of astronomy" (p. 1571), and research already exists, for instance, concerning these celestial patterns (e.g., Plummer, 2009a;Plummer et al, 2011), the dynamics of the Solar System (e.g., Plummer et al, 2020), the phases of the Moon (e.g., Chastenay, 2016); and the day-night cycle (e.g., Kallery, 2011). Yet, despite their relevance, time concepts are not central to these studies.…”
Section: Astronomical Time Concerning Human-scale Time Framementioning
confidence: 99%
“…Additional validity concerns related to external variables and real-world implications are also important to note at later stages of development. We note two examples in the literature where researchers conducted studies to explicitly examine how the learning progression theory mapped to student responses before and after related instruction [34,35].…”
Section: Bear Assessment System and Item Response Theorymentioning
confidence: 99%